RESPIRATORY GYMNASTICS IN REHABILITATION COMPLEXES AFTER MYOCARDIAL INFARCTION - Klapchuk, V. (Rehabilitation and Recreation, 2022)
Goal – to increase the effectiveness of therapeutic exercises by applying special breathing exercises inpatients with myocardial infarction.Methods. Hypoxic tests were performed in two versions: with a breath hold on an inhalation (Stange test)and a breath hold on an exhalation (Gencha test). The results were evaluated by the duration of the breath-holding time and by the rate of chronotropic response of the heart to breath-holding. Chronotropic responsewas determined by the ratio of heart rate after the end of the test to the original heart rate. The inspiratoryand expiratory hypoxic indices were also calculated as the quotient of dividing the duration of breathholding (sec) by the heart rate (beats/min).Results. Under the influence of the rehabilitation complex, an increase in the indices of hypoxic testsof Stange and Gencha was statistically significant in both the main and control groups. But when comparingthem with each other, the final indicators of these samples in the main group were statistically significantlybetter: t = 3.03 and 3.12, respectively, p < 0.01. Calculation of hypoxic indices during the final studyshowed a statistically significant predominance of positive dynamics in the main group by the inspiratoryindex (0.657 ± 0.013 conventional units) when compared with the control (0.552 ± 0.016 conventionalunits) and expiratory index: respectively 0.657 ± 0.013 conv.ed and 0.445 ± 0.011 conventional units(t = 5.09 and 5.94; p < 0.001).Conclusion. In patients after myocardial infarction at the stationary stage of rehabilitation, externalrespiration indexes according to the results of Stange and Gencha hypoxic tests with an assessmentof the chronotropic response of the heart to breath holding, as well as inspiratory and expiratory hypoxicindices obtained during the initial study, were reduced. In order to increase the effectiveness of medicalgymnastics, special breathing exercises were used for half-bed and free motor regimes using elementsof pranayama of the Indian health system of hatha yoga. After the rehabilitation course, the modifiedtherapeutic gymnastics technique that we modified turned out to be more effective than the generallyaccepted one, which has a statistically significant confirmation and therefore allows us to recommend it forimplementation.